Media audience ethics in Islam and Christianity - Solihu, Abdul Kabir Hussain (IIUM Press, 2011)
To safeguard the religio-cultural values of the media audience against the repugnant values often propagandized in the mass media, there has been emphasis on the ethical codes of media producers, reporters and the nature of the message itself. Aiming to achieve the same goal, this study underscores the ethical principles of responsibility and accountability expected from the media audience to uphold as taught in the Islamic and Christian ethics. These principles are drawn upon the active role the media audience plays in information and communication enterprise. To demonstrate this role, the study highlights the theoretical foundation of the audience understanding of the message, cites some legal rights that can be used to challenge the media content or change its course, and identifies some ways of fine-tuning the media contents to conform to one’s value. The study focuses on the television and the Internet due to their predominance in electronic media.